Deficiencies in Natural Killer Cell Numbers, Expansion, and Function at the Pre-Neoplastic Stage of Pancreatic Cancer by KRAS Mutation in the Pancreas of Obese Mice - Kaur, Kawaljit; Chang, Hui-Hua; Topchyan, Paytsar; Cook, Jessica Morgan; Barkhordarian, Andre; Eibl, Guido; Jewett, Anahid (Frontiers in Immunology, 2018)
The combined/synergistic effect of genetic mutation of KRAS in the pancreas and obesity, a life-style factor on suppression of NK cells at the pre-neoplastic stage of pancreatic cancer is not yet investigated and is the subject of this report. Obese mice with KRAS (KC) mutation in the pancreas fed with high fat calorie diet (HFCD) exhibit severe deficiencies in the NK cell expansion and function at the pre-neoplastic stage of pancreatic cancer. Decreased NK cell-mediated cytotoxicity is observed in the peripheral blood, spleen, pancreas and peri-pancreatic-adipose tissue in obese KC mice, whereas in bone marrow an increased NK cell-mediated cytotoxicity is observed when compared to lean WT mice fed with control diet (CD). Obese KC mice on HFCD demonstrated the least ability to expand NK cells or mediate NK cell-mediated cytotoxicity when compared to the other groups of mice. Indeed, the following profile WT/CD>WT/HFCD>KC/CD>KC/HFCD was seen for the ability to expand NK cells or mediate cytotoxicity among 4 groups of mice in spleen, peripheral blood, pancreas and peri-pancreatic-adipose tissue. Sorted NK cells from the splenocytes of 4 groups of mice also exhibited the same profiles for the cytotoxicity as the unsorted splenocytes, and a decreased IFN-γ secretion could be seen in cultures of NK cells from KC mice fed with either CD or HFCD. Cultures of NK cells with autologous monocytes from obese KC mice fed with HFCD exhibited decreased cytotoxicity and IFN- secretion, whereas cultures of allogeneic NK cells from WT mice fed with CD with osteoclasts of obese mice fed with HFCD demonstrated decreased cytotoxicity but augmented IFN- secretion. Increased IL-6 along with the decreased IFN-γ as well as cell-mediated cytotoxicity seen in the NK-adipose tissue interaction of KC/HFCD mice may provide safe microenvironment for the expansion of pancreatic tumors.